PENENTANGAN TIONGKOK TERHADAP KOREA SELATAN DALAM PENGADAAN TERMINAL HIGH ALTITUDE AREA DEFENSE (THAAD) DI KOREA SELATANTAHUN 2016 - ", Habiburrahman; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The tensions on the Korean Peninsula have had an impact on the surrounding countries. North Korea with their nuclear weapons development makes South Korea feel their country is threatened. North Korea's nuclear test in early 2016 makes South Korea put highly concern on this issue, then prompted South Korea to re-consider and approve suggestions from the United States to place Terminal High Altitude Area Defense (THAAD) in South Korea. The achievement of the agreement with the United States then get opposition from China. According to China, THAAD can not provide solutions for the situation on the Korean peninsula. This research uses a realism perspective which is then supported by the national security theory of Barry Buzzan and some concepts such as the regional security complex, and security dilemma. This study also used a nation-state analysis level with a research focus on the factors that make adult China THAAD in South Korea, and all of data, arguments, fact in this research afterwards using a qualitative explanation method.This research then formulates answer of the research question related to China’s opposition to THAAD. There are three important points that led to china’s opposition to THAAD, first, including China’s attention to the THAAD’s radar capabilities that could harm china’s national security, second, the existence of THAAD provide a strategic dilemma for china to face their allies North Korea, and third the existence of THAAD also impacted China’s security dilemma on south korea and their allies.Keywords: Korean Peninsula, South Korea, China, National Security, Opposition, THAAD